The Fructoborates: Part of a Family of Naturally Occurring Sugar–Borate Complexes—Biochemistry, Physiology, and Impact on Human Health: a Review - Hunter, John M. (Biol Trace Elem Res, 2018)
Sugar–borates (SBs) are mono- or di-sugar–borate esters (SBEs) comprised of one or two monosaccharide molecules linked to a boron (B) atom. SBEs occur naturally in commonly consumed herbs, vegetables, fruits, seeds, and nuts and, other than greatly varying levels of B found in local drinking water, are the primary natural dietary sources of B-containing molecules in humans. To date, the most studied SBE is calcium fructoborate (CaFB). CaFB represents an important example of how organic B-containing molecules are significantly distinct from their inorganic counterparts. During these past two decades, CaFB has been researched for its physical and biochemical characteristics, safety, and clinical outcomes. Results of these researches are presented and discussed herein. CaFB has been characterized using Fourier-transform infrared (FTIR) spectroscopy, thermogravimetric analysis (TGA), high-performance thin-layer chromatography (HPTLC), nuclear magnetic resonance (NMR), liquid chromatography–multistage accurate mass spectrometry (LC-MSn), X-ray diffraction (XRD), Raman spectroscopy, and inductively coupled plasma (ICP) in non-biological and biological specimens. Potential health benefits of CaFB have been clinically investigated in pilot and efficacy studies demonstrating (i) significant reductions in knee discomfort and improved flexibility within 7, 14, and 90 days and (ii) significant effect on blood levels of inflammatory, cardiovascular, and other biomarkers. These studies support the use of CaFB as a dietary supplement for the management of joint discomfort. CaFB is presented here in order to illustrate how physiological benefits are imparted by distinct organic boron-containing molecules rather than solely by the element B itself. Considering recent National Health and Nutrition Examination Survey (NHANES) data reporting increases in age-related joint pain and an increasing elderly demographic, SBEs offer potential for safe, natural, and effective management of joint discomfort and improved mobility in human and animal health applications. Several of these studies may also open new opportunities for use of SBEs for health benefits beyond joint health.